Thermo-kinetik investigation of crystallizing process of chromium vanadium white irons - S. S. Gurin; Ju. A. Saunin (Литьë и металлургия, 2002)
The refinement of the structure of chromium- vanadium cast irons, as well as of other alloys, appreciably increases their operation characteristics. One of the methods of favorable structure receiving is high freezing rate of alloy, what is shown in the work.